The effect of sports tourism and recreation sector perception on student career plans - ALPULLU, AYTEKİN (My University, 2018)
In this study, the effects of the recreation and sports tourism perception formed by the 3rd and 4th grade students, who take recreation and sports tourism courses at Marmara University Sports Sciences Faculty by taking place in the sector as a customer or employee as well as the education they get at the university, on their career plans are investigated. During the study, the quantitative research method was adopted and the questionnaire that Olcay and Düzgün (14) used in their study is utilized. As a result of the study carried out with the sample group of 70 people in order to see which gender is more suitable for the sector, no significant difference was found among the students who were considering to choose recreation and sports tourism as their career targets. There was also no significant difference between sexes regarding the negative impact of irregular and intense working conditions of the sector on family. In addition, in terms of career, it has been found that the ratio of those who see the sector as suitable for being employed for along times high. As a result of the analysis carried out at this high rate, the amount of those who think about graduate education calls attention.
Keywords: Spor Bilimleri